Agminated blue nevi: a case series and updated dermoscopic review - Sławińska, Martyna; Balicka, Urszula; Kamińska-Winciorek, Grażyna; Sikorska, Monika; Nowicki, Roman; Sobjanek, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Blue nevi, usually presenting as solitary, bluish, asymptomatic macules or nodules, are formed by collections of dermal melanocytes that failed to complete their migration from the neural crest to the dermo-epidermal junction. The term “agminated blue nevi” refers to multiple lesions grouped, linear, or arranged in a blashkoid distribution. It is a relatively rare phenomenon with less than 35 cases reported in the literature, but only 14 cases with dermoscopic features. We report another 4 cases along with an updated dermoscopic review.